To Evaluate and Compare the Release of Nickel, Chromium, and Titanium from Three Different Commercially Available Stainless steel Crowns at Different pH Levels: An In vitro Study - Dedeepya Devi Santapuri; Satyam Martha; R Punithavathy; K Haritha; Harika Chowdary Manukonda; Manideep Yadlapalli (Journal of Pharmacy and Bioallied Sciences)
Background: Stainless steel crowns (SSCs) are widely used in pediatric dentistry; however, their long-term biocompatibility remains a concern due to potential ion release. The oral environment’s varying pH and temperature may influence the leaching of metal ions such as nickel, chromium, and titanium. Aim: To estimate and compare the release of nickel, chromium, and titanium from three commercially available SSCs in artificial saliva at different pH levels (5.5, 6.5, and 7.5) over various time intervals (1, 3, and 6 months). Materials and Methods: Three different brands of SSCs were selected and grouped accordingly. Each group was further subdivided into three subgroups based on the pH of the artificial saliva (5.5, 6.5, and 7.5). The crowns were immersed in artificial saliva and incubated at 37°C. Samples were collected at 1, 3, and 6 months and analyzed using a spectrophotometer to measure the concentration of nickel, chromium, and titanium ions released, reported in parts per million (ppm). Statistical analysis was conducted to assess differences in ion release between groups and across time points. Results: There was a statistically significant variation in the release of metal ions across different pH levels and time intervals. Nickel and chromium were consistently detected in all groups, while titanium release was minimal. The ion release remained within biologically acceptable limits and was not considered toxic. Conclusion: All tested SSCs released measurable amounts of nickel and chromium, with variations based on pH and duration.